2010
DOI: 10.1007/s00520-010-0894-x
|View full text |Cite
|
Sign up to set email alerts
|

Topical curcumin can inhibit deleterious effects of upper respiratory tract bacteria on human oropharyngeal cells in vitro: potential role for patients with cancer therapy induced mucositis?

Abstract: Curcumin, in clinically relevant concentrations for topical use, displayed strong antibacterial effect against a facultative upper respiratory tract pathogen by inhibiting bacterial growth, adherence, invasion, and pro-inflammatory activation of upper respiratory tract epithelial cells in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 35 publications
0
28
2
Order By: Relevance
“…63 Turmeric/curcumin has also been reported to possess antimicrobial effects, including against the clinically relevant methicillinresistant Staphylococcus aureus strains 64 With regard to the bacteria involved in the process of oral mucositis, in vitro studies with Moraxella catarrhali, a facultative upper respiratory tract pathogen have shown that curcumin possess bactericidal effects to inhibit bacterial adherence and invasion to Detroit 562 (pharyngeal cells) and to reduce Mcat-induced pro-inflammatory activation by suppressing release of pro-inflammatory cytokine IL-8. 65 Pre-incubation of Detroit cells with 200 µM curcumin for 5 to 60 minutes resulted in complete suppression of the release of tumor necrosis factor-α, IL-6, IL-8, monocyte chemoattractant protein 1, granulocyte macrophage-colony stimulating factor, and vascular endothelial growth factor. 65 Additionally, the investigators have also observed that repetitive exposure to curcumin caused recurring suppression of cytokine/ chemokine expression.…”
Section: Discussionmentioning
confidence: 97%
“…63 Turmeric/curcumin has also been reported to possess antimicrobial effects, including against the clinically relevant methicillinresistant Staphylococcus aureus strains 64 With regard to the bacteria involved in the process of oral mucositis, in vitro studies with Moraxella catarrhali, a facultative upper respiratory tract pathogen have shown that curcumin possess bactericidal effects to inhibit bacterial adherence and invasion to Detroit 562 (pharyngeal cells) and to reduce Mcat-induced pro-inflammatory activation by suppressing release of pro-inflammatory cytokine IL-8. 65 Pre-incubation of Detroit cells with 200 µM curcumin for 5 to 60 minutes resulted in complete suppression of the release of tumor necrosis factor-α, IL-6, IL-8, monocyte chemoattractant protein 1, granulocyte macrophage-colony stimulating factor, and vascular endothelial growth factor. 65 Additionally, the investigators have also observed that repetitive exposure to curcumin caused recurring suppression of cytokine/ chemokine expression.…”
Section: Discussionmentioning
confidence: 97%
“…The human pharyngeal epithelial cell line Detroit 562 (ATCC CCL 138) was cultured as published earlier in MEM supplemented with 10% of heat-inactivated fetal calf serum (FCS), 2 mM of L-glutamine (Invitrogen, Basel, Switzerland), 1% sodium bicarbonate (Invitrogen, Basel, Switzerland), 1× MEM non-essential amino acid solution (Sigma, St. Louis, MO, USA), 1 mM sodium pyruvate (Sigma, St. Louis, MO, USA), 100 μg/ml streptomycin and 100 U/ml penicillin at 37°C in 5% CO 2 [26]. Cells were grown in 24-well plates to a confluent cell layer (≈3×10 5 cells per well).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it exhibits significant antimicrobial activity in vitro against a number of Gram-negative and Grampositive bacteria such as Bacillus subtilis, Escherichia coli, Helicobacter pylori, Salmonella enterica serovar Typhimurium, and some Staphylococcus aureus strains [12][13][14][15]. In vitro experiments with human oropharyngeal cells have demonstrated that curcumin has considerable inhibitory effect against bacteria in the upper respiratory tract, thus, affecting their growth, adherence, invasion, and pro-inflammatory activation [16].…”
Section: Introductionmentioning
confidence: 99%